Saphenous Nerve Schwannoma: A Rare Differential Diagnosis of Knee Pain in Children - Amine Cherraqi MD; Siham El Haddad MD PhD; Ola Messaoud MD; Hajar Andour MD; Mohammed Tbouda MD; Naoual El Ansari MD; Amina KILI MD PhD; Laila Hessissen MD PhD; Nazik Allali MD PhD; Latifa Chat MD PhD (SAGE Publishing, 2023)
Schwannomas are uncommon benign tumors of the peripheral nerves with a low risk of malignant transformation. They rarely affect children, can affect any part of the body but rarely occur in the lower extremity and typically present with a palpable mass, pain or neurological signs. Imaging helps to orient the diagnosis and anatomopathological examination helps to confirm it. We report a case of a 12-year-old girl who presented with left knee pain with subcutaneous mass overlying the tibial tuberosity medially. Clinical examination revealed a positive Tinel's sign. Magnetic resonance imaging (MRI) of the knee was performed, which revealed an encapsulated subcutaneous soft tissue mass overlying the tibial tuberosity medially, eccentric to the course of the infrapatellar branch of the saphenous nerve. The patient was operated with total intracapsular excision of the lesion and the anatomopathological study of the surgical specimen came back in favor of a schwannoma. Postoperatively, the patient showed a good recovery with disappearance of pain and swelling.